Pengelolaan Hotel Syariah Menurut Fatwa DSN-MUI Nomor 108 Tahun 2016 Tentang Pedoman Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah (Studi Kasus di Hotel Ratna Syariah Kota Probolinggo) - Hillyah Sadiah, Hillyah (Universitas Muhammadiyah Surabaya, 2019)
This study examines about how the operation of the Ratna Syariah Hotel from its product, service, and management aspects according to the DSN-MUI fatwa and the principles of Sharia Economic Law which include the principles of tauhid, the principle of justice, the principle of ta'awun (help), the principle of khilafah, and the principle of maslahah. This research is limited to the following problems: (1) How are sharia-based products, services, and management carried out by Hotel Ratna Syariah in the City of Probolinggo according to the DSN-MUI fatwa on Guidelines for Implementing Sharia-Based Tourism Principles? (2) How are sharia-based products, services and management implemented by Hotel Ratna Syariah in the City of Probolinggo according to the Principles of Sharia Economic Law? This type of research is field research, namely research activities conducted at Ratna Syariah Hotel located in the city of Probolinggo. To understand and analyze the object under study, several approaches are used as follows: (1) Legislative approach, meaning that the operational implementation of Sharia Ratna Hotels in the city of Probolinggo will be analyzed intensively, deeply, in detail and comprehensively based on the legal regulations governing this matter is the DSN-MUI fatwa and also Islamic sharia principles. The data collection technique is done by interview, observation, and documentation.The results of this study are: (1) In general, the products offered are in accordance with DSN-MUI fatwa Number 108 of the third section which contains general principles of sharia tourism administration, and also the fifth section which contains provisions related to sharia-based hotel management which includes provisions regarding products in sharia hotels; the services provided are in accordance with the fifth part of DSN-MUI fatwa, which contains the provisions related to sharia-based hotel management which include provisions regarding products and services, except the seventh point which regulates that sharia hotels must use the services of Islamic Financial Institutions in performing services ( financial transactions); and the management carried out by the Hotel Ratna Syariah is in accordance with the third part of the DSN-MUI fatwa, which contains the general principles of implementing sharia tourism; the fourth part which contains the contract provisions that must be used in the implementation of the sharia tourism business; and the fifth part which contains provisions related to sharia-based hotel management which includes provisions regarding products, services, and operations, except point six in this section; (2) the operationalization of products, services, and management of Sharia Ratna according to the results of the research of the author in accordance with the principles in Sharia Economic Law which includes the principles of tauhid, the principle of justice, the principle of ta'awun (help), the principle of khilafah, and principles maslahah.Â Keywords: Sharia Hotels, Fatwas, DSN-MUI, Sharia Principles, Sharia Economic Law.